EVALUACIÓN DE DOS MÉTODOS DE EXTRACCIÓN DE PECTINA A PARTIR DE DOS VARIEDADES DE PITAHAYA AMARILLA (Hylocereus megalantus) ROJA (Hylocereus undatus) - ALAY SUAREZ , BRIGGITTE KASSANDRA (2025)
In 2023, pitahaya exports increased by 72% to key markets such as China and the United States, generating overproduction of this fruit. A drastic drop in prices, which are often below production costs, results in large quantities of pitahaya being wasted, ending up as livestock feed or simply discarded